Focusing the future of farming on agroecology - Alan J. Franzluebbers; Ole Wendroth; Nancy G. Creamer; Gary G. Feng (Agricultural & Environmental Letters, 2020)
Abstract The future of humanity and how agriculture can continue to support the food and fiber needs of a burgeoning population are threatened by agriculture's persistent negative effects on the environment. Essential natural resources that will be needed in increasingly greater capacity are being undermined by agricultural practices that continue to deplete the soil resource base, pollute freshwater and coastal estuaries needed for life support, reduce habitat to support biodiversity, and emit harmful greenhouse gases that compromise our ability to withstand changes to the climate. Solutions to these problems are available in known and increasingly well documented approaches using agroecological principles that manage food production in harmony with nature, not against it. This commentary provides a message that we should be seeking healing of our planet, not just less harm than in the past. It is an important distinction that needs to be considered for the future health of people and the planet.